Probing on the Relationship between Students' Self-Confidence and Self-Efficacy while engaging in Online Learning amidst COVID-19 - Quiana Althea Blanco; Mark Lyster Carlota; Ashley Janine Nasibog; Beatriz Rodriguez; Xydel Vie Saldaña; Elaisha Carmel Vasquez; Flordeliza Gagani (Newinera Publisher, 2020)
The onslaught of the Coronavirus-19 disease around the world has shaken the physical and mental well-being of the global citizenry. The student populace in particular faces added burdens and struggles in light of the pandemic due to the abrupt shift in learning modality and educational delivery to cope with the